2020
DOI: 10.4252/wjsc.v12.i7.562
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy regulates fate of cancer stem cells through reactive oxygen species

Abstract: Photodynamic therapy (PDT) is an effective and promising cancer treatment. PDT directly generates reactive oxygen species (ROS) through photochemical reactions. This oxygen-dependent exogenous ROS has anti-cancer stem cell (CSC) effect. In addition, PDT may also increase ROS production by altering metabolism, endoplasmic reticulum stress, or potential of mitochondrial membrane. It is known that the half-life of ROS in PDT is short, with high reactivity and limited diffusion distance. Therefore, the main target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 223 publications
(202 reference statements)
1
29
0
Order By: Relevance
“…This nding is similar to previous studies who reported a bene cial role for PDT in treating several types of cancer including including glioblastomas, lung, esophageal, bladder, colorectal and nasopharyngeal carcinomas [32]. PDT-generated ROS can change the activity of CSC markers Oct4 and Sox2 [21]. Furthermore, ROS attacks DNA causing point mutations in key genes such as Ras [33] and p53 [34] which regulate several pathways in the cell including regulate proliferation, differentiation and apoptosis [35].…”
Section: Discussionsupporting
confidence: 89%
“…This nding is similar to previous studies who reported a bene cial role for PDT in treating several types of cancer including including glioblastomas, lung, esophageal, bladder, colorectal and nasopharyngeal carcinomas [32]. PDT-generated ROS can change the activity of CSC markers Oct4 and Sox2 [21]. Furthermore, ROS attacks DNA causing point mutations in key genes such as Ras [33] and p53 [34] which regulate several pathways in the cell including regulate proliferation, differentiation and apoptosis [35].…”
Section: Discussionsupporting
confidence: 89%
“…Although both PDT reaction type I and type II depend on oxygen, the subcellular oxygen concentration within the tumor microenvironment determines the reaction type that occurs. The efficiency of PDT to induce tumor cell destruction relies on the concentration and subcellular internalization of the photosensitizers and the production of sufficient cytotoxic singlet molecular oxygen and ROS [30]. The principle of PDT also consists of three steps, however it varies from PDD: (a) internalization of photosensitizer in the tumor cells, (b) application of light, and (c) interaction with molecular oxygen.…”
Section: Principle Of Photodynamic Diagnosis and Photodynamic Therapymentioning
confidence: 99%
“…Targeted photosensitizers are used in lesions to accept the corresponding wavelength of visible optical irradiation. After stimulation, the energy transfer, and electron transfer process, the surrounding oxygen molecules with chemical properties of singlet oxygen, superoxide free radicals, and reactive oxygen species, such as material and substrate molecule free radicals, are applied to biological macromolecules, eventually lead to death or apoptosis of tumor cells [ 94 ]. The fully active MOF triggers the ferroptosis mechanism to facilitate photodynamic antitumor therapy (a fully active MOF nanocarrier contains disulfide, which is used to encapsulate the photosensitizer Ce6).…”
Section: Tumor Therapy Based On Nonepigenetic and Epigenetic Of Fementioning
confidence: 99%